An Euroheart-Based Percutaneous Coronary Intervention Registry in Vietnam: Design, Rationale, and Preliminary Results. - Hoang Vu, V.; Nguyen, Khang Duong; Duong, B. T.; Pham, Ngoc Minh; Reid, Christopher M; Truong, B. Q.; Norman, Richard (2025)
BACKGROUND: As a cardiac interventional procedure, percutaneous coronary intervention (PCI) is increasingly becoming the most widely adopted across the globe. With increasing implementation in practice, the use of PCI registries to evaluate safety and effectiveness has grown internationally. Standardization across registries in relation to common data elements will allow comparison between outcomes in different populations. AIMS: This study is to enhance the understanding of PCI practices and outcomes in a developing country context. This registry is among the first of its kind in Vietnam, providing an unprecedented level of detail on procedural characteristics, patient outcomes, and quality metrics in a population that has been underrepresented in global cardiovascular research. METHODS: This protocol reports a prospective, single-center, PCI registry based on the EuroHeart data set standards for acute coronary syndrome/PCI, conducted at University Medical Center Ho Chi Minh City, Vietnam. It describes the data collection and analysis process and presents baseline characteristics of the first enrollees. RESULTS: From December 2023 to October 2024, we enrolled 1168 PCI patients, with a mean age of 64.1% ± 11.7% and 68.8% being male. Hypertension emerged as the most prominent risk factor. In addition, 27.8% of the population received a final diagnosis of ST-elevation myocardial infarction. The mean baseline Seattle Angina Questionnaire-7 summary score was 60.8 ± 16.4. CONCLUSION: Establishing a registry is an important step in assuring quality and safety in the provision of PCI. A PCI registry based on EuroHeart data set standards will align with international efforts. In-hospital results also demonstrate early success in implementing the PCI registry management.